1993
DOI: 10.1164/ajrccm/147.4.839
|View full text |Cite
|
Sign up to set email alerts
|

Oral Leukotriene Inhibitor (MK-886) Blocks Allergen-induced Airway Responses

Abstract: To elucidate the role of leukotrienes (LT) in allergic asthma in humans the effect of MK-886, an LT biosynthesis inhibitor, was evaluated on antigen-induced early (EAR) and late (LAR) asthmatic reactions and bronchial responsiveness to histamine. Eight atopic men participated in a two-part, double-blind, placebo-controlled, crossover trial. MK-886 was administered in two oral doses of 500 mg and 250 mg, 1 h before and 2 h after allergen inhalation, respectively. Biochemical effects of MK-886 were evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(72 citation statements)
references
References 22 publications
1
69
0
2
Order By: Relevance
“…2) and by the activation of 5-LO through its phosphorylation by the p38 MAPK-activated protein kinase MAPKAP-K2 (39). Interestingly, FLAP inhibitors have demonstrated benefits in allergic asthma clinical trials (29), whereas naturally occurring mutations in the promoter of region of 5-LO may be associated with asthma (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) and by the activation of 5-LO through its phosphorylation by the p38 MAPK-activated protein kinase MAPKAP-K2 (39). Interestingly, FLAP inhibitors have demonstrated benefits in allergic asthma clinical trials (29), whereas naturally occurring mutations in the promoter of region of 5-LO may be associated with asthma (40).…”
Section: Discussionmentioning
confidence: 99%
“…1). Moreover, an inhibitor of 5-LO, MK886 (29), attenuated the IL-17-conditioned LMVEC medium-driven neutrophil migration when added to LMVECs prior to their stimulation with IL-17 (Fig. 2G).…”
Section: Il-17 Promotes Selective Migration Of Neutrophilsmentioning
confidence: 92%
“…For example, the 5-LO inhibitor, zileuton, showed progressive improvement on respiratory measures and decreased asthma symptoms over a 4-week period (Israel et al, 1993). In addition, MK-886 and MK-591, two distinct FLAP inhibitors, prevented LT production and inhibited early and late-phase response to allergen challenge (Friedman et al, 1993;Diamant et al, 1995). MK-0591 has also shown efficacy in chronic asthma studies (Young, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of CysLT 1 -receptor antagonists, including montelukast, are approved for treatment of asthma and allergic rhinitis. Three FLAP inhibitors have been evaluated in human clinical trials, including MK-866 (Friedman et al, 1993), MK-591 (Diamant et al, 1995), and BAYX-1005 (Hamilton et al, 1997), and all showed efficacy against the early and late phases of allergen-induced lung-volume decline. Although none of these FLAP inhibitors is marketed, MK-591 was efficacious in chronic asthma (Young, 1999).…”
mentioning
confidence: 99%
“…Among drugs which inhibit leukotriene biosynthesis, the FLAP antagonists MK-886 [94], MK-591 [171] and BAY ϫ 1005 [95] have been documented to be potent inhibitors of leukotriene formation when given to humans in vivo [171][172][173]. The 5-lipoxygenase inhibitor, zileuton (Table 1), is now registered in the US for the treatment of asthma.…”
Section: Pharmacological Control Of the Leukotriene Pathwaymentioning
confidence: 99%